Evaluation of Municipal solid waste fly ash as a blended cement material - Goh, Chia Chia. (2008)
Incineration has become one of the principal methods for reducing the volume of municipal solid waste before disposal, especially, in large cities throughout the world. In Singapore, the total amount of solid waste generated in 1999 was 2.79 million tons. About 85 percent of this were incinerated. After incineration, the solid waste was reduced to about 20 percent by weight in the form of municipal solid waste fly ash (MFA) and other residues.